The PD‐1/PD‐L1 axis may be aberrantly activated in occupational cholangiocarcinoma - Sato, Yasunori; Kinoshita, Masahiko; Takemura, Shigekazu; Tanaka, Shogo; Hamano, Genya; Nakamori, Shoji; Fujikawa, Masahiro; Sugawara, Yasuhiko; Yamamoto, Takatsugu; Arimoto, Akira; Yamamura, Minako; Sasaki, Motoko; et al. (Pathology international, 2017)
An outbreak of cholangiocarcinoma in a printing company was reported in Japan, and these cases were regarded as an occupational disease (occupational cholangiocarcinoma). This study examined the expression status of programmed death‐1 (PD‐1) and programmed death‐ligand 1 (PD‐L1) in occupational cholangiocarcinoma. Immunostaining of PD‐1, PD‐L1, CD3, CD8, and CD163 was performed using tissue sections of occupational cholangiocarcinoma (n = 10), and the results were compared with those of control cases consisting of intrahepatic (n = 23) and extrahepatic (n = 45) cholangiocarcinoma. Carcinoma cells expressed PD‐L1 in all cases of occupational cholangiocarcinoma, whereas the detection of PD‐L1 expression in cholangiocarcinoma cells was limited to a low number of cases (less than 10%) in the control subjects. In cases of occupational cholangiocarcinoma, occasional PD‐L1 expression was also noted in precancerous/preinvasive lesions such as biliary intraepithelial neoplasia and intraductal papillary neoplasm of the bile duct. Additionally, tumor‐associated macrophages and tumor‐infiltrating T cells expressed PD‐L1 and PD‐1, respectively. The number of PD‐L1‐positive mononuclear cells, PD‐1‐positive lymphocytes, and CD8‐positive lymphocytes infiltrating within the tumor was significantly higher in occupational cholangiocarcinoma compared with that in control cases. These results indicate that immune escape via the PD‐1/PD‐L1 axis may be occurring in occupational cholangiocarcinoma.